how to solve a problem

Algebra
Tutor: None Selected Time limit: 1 Day

-1/6(x-12)+1/2(x+2)=x-1

Sep 28th, 2014

when expandend it becomes

-x/6+2+x/2+1 = x-1

get the like terms together to have

-x/6+x/2-x =-1-2-1

(-2x)/3 =-4

-2x= -4*3

-2x=-12

divide each side by -2 to get

-2x/2 =-12/-2

x= +6

thank you best me please

Sep 28th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Sep 28th, 2014
...
Sep 28th, 2014
Mar 30th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer